Il-6 and UGT1A1 variations may related to furosemide resistance in heart failure patients - GÜNEY, AHMET İLTER; SÜNBÜL, MURAT (My University, 2023)
Furosemide is a diuretic and is used for the treatment of patients with heart failure (HF). It has been found that in some HF patients, the drug does not treat patients efficiently. This condition is named as furosemide resistance. In this study, it is aimed to investigate the relationship between UDP-glucuronosyltransferase 1 (UGT1A1) and interleukine-6 (IL-6) variations with furosemide resistance in HF patients. Sixty HF patients using furosemide (patient group) and 30 healthy individuals (control group) were enrolled in this study. Patients were divided into two subgroups as non-responders (furosemide resistant) group (n = 30) and the responders (non-resistant) group (n = 30) according to the presence of furosemide resistance (n = 30). Variations in the first exon of UGT1A1 and rs1800795 and rs1800796 variations in IL-6 were analyzed by direct sequencing and real-time polymerase chain reaction (RT-PCR), respectively. The effects of newly detected mutations on 3-D protein structure were analyzed by in silico analysis. At the end of the study, 11 variations were detected in UGT1A1, of which nine of them are novel and eight of them cause amino acid change. Also, rs1800795 and rs1800796 variations were detected in all the groups. When patient and control groups were compared with each other, rs1800796 mutation in IL-6 was found statistically high in the patient group (p = 0.027). When the three groups were compared with each other, similarly, rs1800796 mutation in IL-6 was found statistically high in the non-responders group (p = 0.043). When allele distributions were compared between the patient and control groups, the C allele of rs1800795 mutation in IL-6 was found statistically high in the patient group (p = 0.032). When allele distributions were compared between the three groups, 55T-insertion in UGT1A1 was found statistically high in the non-responders group (p = 0.017). According to in silico analysis results, two variations were found deleterious and six variations were detected as probably damaging to protein functions. Our study may contribute to the elucidation of pharmacogenetic features (drug response–gene relationship) and the development of individual-specific treatment strategies in HF patients using furosemide.
Keywords: Tıp; Histoloji-Embriyoloji; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Histology and Embryology; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); HÜCRE BİYOLOJİSİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; GENETİK VE KALITIM; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; CELL BIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; GENETICS & HEREDITY; Biyokimya; Moleküler Biyoloji; Genetik; Klinik Biyokimya; Hücre Biyolojisi; Biochemistry; Molecular Biology; Genetics; Clinical Biochemistry; Cell Biology; diuretic resistance; furosemide; heart failure; IL-6; UGT1A1; INTERLEUKIN-6 GENE POLYMORPHISMS; UGT1A1-ASTERISK-28 ALLELE; CARDIOVASCULAR-DISEASE; RISK; ASSOCIATION; SUSCEPTIBILITY; POTASSIUM; SMOKING; ONSET